2021
DOI: 10.3899/jrheum.201663
|View full text |Cite
|
Sign up to set email alerts
|

Majeed Syndrome: Five Cases With Novel Mutations From Unrelated Families in India With a Review of Literature

Abstract: Chronic recurrent multifocal osteomyelitis (CRMO) (OMIM # 259680) is a common genetically heterogenous autoinflammatory disease of the bone, first described in 1972 (1) with the typical mean age at diagnosis 9 years (2). Syndromic CRMO presents early in life and includes three monogenic recessively inherited conditions: Majeed syndrome (MJS), deficiency of interleukin-1 receptor antagonist (DIRA), and CRMO-related to the FBLIM1 gene (2).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The individuals we described had clinical features comparable to the previously reported individuals. Some of the atypical features reported previously include recurrent abdominal pain, recurrent diarrhoea, recurrent unilateral serous discharge, and erythema nodosum (Chavan et al ., 2021).…”
Section: Discussionmentioning
confidence: 88%
“…The individuals we described had clinical features comparable to the previously reported individuals. Some of the atypical features reported previously include recurrent abdominal pain, recurrent diarrhoea, recurrent unilateral serous discharge, and erythema nodosum (Chavan et al ., 2021).…”
Section: Discussionmentioning
confidence: 88%
“…In some patients affected by CRMO, single-gene defects have been identified. Clinical geneticists have also identified some similarities with Majeed syndrome, which is extremely rare, being described in only 24 individuals from 10 families, and is characterized by recurrent episodes of fever and osteomyelitis, and dermatitis ( 33 , 34 ).…”
Section: Etio-pathogenesismentioning
confidence: 99%
“…MJS presents with early-onset recurrent osteitis and multifocal osteomyelitis, and congenital dyserythropoietic anemia. A study in India showed that patients with MJS also had other unreported symptoms, including abdominal pain, recurrent diarrhea and ear secretions [ 65 ]. Lesional skin biopsies show a dermal neutrophilic infiltrate with edema of the upper dermis without histologic evidence of vasculitis.…”
Section: Introductionmentioning
confidence: 99%